Evaluation of the dental casts measurements using caliper and 3D laser scanning : preliminary results - Zie Zie Azeanty Tahir; Halim Setan, 1957-; Zulkepli Majid; Deni Suwardhi; Abd. Rani Samsuri; International Symposium and Exhibition on Geoinformation (2006 : Selangor) (Skudai : Universiti Teknologi Malaysia, 2006)
42